A schistosome cAMP-dependent protein kinase catalytic subunit is essential for parasite viability. - Brett E Swierczewski; Stephen J Davies (PLoS Neglected Tropical Diseases)
Eukaryotes, protozoan, and helminth parasites make extensive use of protein kinases to control cellular functions, suggesting that protein kinases may represent novel targets for the development of anti-parasitic drugs. Because of their central role in intracellular signaling pathways, cyclic nucleotide-dependent kinases such as cAMP-dependent protein kinase (PKA) represent promising new targets for the treatment of parasitic infections and neoplastic disorders. However, the role of these kinases in schistosome biology has not been characterized and the genes encoding schistosome PKAs have not been identified. Here we provide biochemical evidence for the presence of a PKA signaling pathway in adult Schistosoma mansoni and show that PKA activity is required for parasite viability in vitro. We also provide the first full description of a gene that encodes a PKA catalytic subunit in S. mansoni, named SmPKA-C. Finally we demonstrate, through RNA interference, that SmPKA-C contributes to the PKA activity we detected biochemically and that inhibition of SmPKA-C expression in adult schistosomes results in parasite death. Together our data show that SmPKA-C is a critically important gene product and may represent an attractive therapeutic target for the treatment and control of schistosomiasis.